Bireysel emeklilik fonları ile yatırım fonlarının getiri profillerinin istatistiksel olarak karşılaştırılması - Ulukaya, Demet (My University, 2010)
A sentence is a unit of language expression. The thoughts can not be transferred completely without sentence. The indicator of that a language is learned fully is in direct proportion to the speakers’ skills of construction of sentence. The textbooks are important for sentence teaching. The textbooks are the basic sources which are used for improving planned and programmed education teaching process. Therefore sentences in the Turkish textbooks must be suitable for the level of students in terms of number, length and variety. This study is prepared to examine 6, 7, 8 grade Turkish textbooks so that to learn sentence variety in Turkish textbooks in this way. Turkish textbooks are compulsory sources to carry out Turkish teaching. According to Turkish teaching program the sentence is teached in various ways in 8 grade textbook. The sentence is a tool to reinforce and evaluate other grammar issues in 6-7 grade textbooks. In the first part of the research were given objectives of the study and problem situations. In the second part were studied sentence, sentence elements, sentence types, syntax teaching and sentence subjects in the textbooks. In the third part the method of research is mentioned, in the fourth part the findings and comments gained from research results took place. In the fifth part the last part the results of research and suggestions are presented. The findings gained from the results of research can be summarized like that: 1. In the primary education 6-7-8 grade textbooks it is more used verb sentence than noun sentence, regular sentence than inverted sentence, simple sentence than compound sentence. 2. Coordinate sentence, conjunctive sentence and elliptic sentences are not given more space in textbooks. 3. There are examples of all types of sentences in the Turkish textbooks. Key Words: Sentence, sentence varietions, syntax teaching, Turkish textbook

A STATISTICAL COMPARISON BETWEEN INCOME PROFILES OF PRIVATE PENSION FUNDS AND MUTUAL FUNDS The evaluation of investments is very important for individuals and institutions. It is necessary for individuals and institutions to bring the revenue back in the economy. These investments, however, need to produce benefits for individuals and institutions, and create a confidence against risks. Mutual funds are therefore the most important instruments of diversifying investments against risks. The content of investment funds includes various investment instruments and brings revenue as per risks. Because of that, individual persons and institutions can diversify the risk and bring their revenue to an optimal level. A similar view of the feature of mutual funds can be found in risk return profiles. Risk return profiles are developed to create an additional income for individuals in their future lives such as mutual funds. The market invests similar to investment funds in investment instruments and tries to reach an optimal level for revenue while distributing. Because of their same usage of investment instruments, investment funds and income profiles have many similarities. On the other hand, unlike investment funds, income profiles are created for individual persons to bring an additional income and have various advantages. 384 mutual funds and income profiles (112 Type A funds, 163 Type B funds and 103 risk return profiles) evaluated in factor analysis (Taking into account 1511 weekdays between 01.01.2004 and 31.12.2009). There are two main purposes of factor analysis. The first purpose is to determine a group of funds with similar characteristics and to prove that their semantic association is providing a statistical characteristic. In the second place is to find new characteristics by using their relation. This study tries to find out groups of variable funds which cannot be seen while making the factor analysis on the 384 variable funds by observing 1511 weekdays. This study shows graphics of funds which are at the same factor as factor analysis and proves that they own similar gain profits. It emerges, funds with same established characteristics gather in similar statistical groups. Therefore the diversity of funds does not show wider revenue diversity. The study is formed in 5 sections. The first section examines investment funds. The second section examines risk return profiles. The comparison of investment funds and risk return profiles is in the third section. The forth section examines the main structure of factor analysis, while the fifth section is examining the factor analysis of investment funds and risk return profiles in Turkey. vate Pension Funds, Mutual Funds and Factor Analysis
Keywords: Bireysel Emeklilik; Sigortacılık; Yatırım Fonları